Improvement of Cochineal Extract (Dactylopius coccus Costa) Properties Based on the Green Synthesis of Silver Nanoparticles for Application in Organic Devices. (21st May 2018) - Stael, Carina; Cruz, Ricardo; Naranjo, Blanca; Debut, Alexis; Angulo, Yolanda
Abstract : The UV-Vis absorption and conductivity properties of the organic sample cochineal ( Dactylopius coccus Costa) were modified by using it as a reducing agent in the biosynthesis of silver nanoparticles. This was done in a straightforward way in order to allow its possible application in organic devices. The biosynthesized solution exhibited a hybrid material with a UV-Vis absorbance range from 205 to 650 nm. The sizes of silver nanoparticles of the hybrid material were between 5 and 10 nm. X-ray diffraction (XRD) revealed silver structures, when samples were dried at 100°C. At 40°C, the structures detected were chlorargyrite (AgCl) and silver oxide (Ag2 O). The nucleation and subsequent growth of the hybrid thin film on the substrates indicated an increase of clusters and roughness in comparison to thin films made solely from cochineal. The thin films of hybrid materials showed an improvement of 40% in their electrical potential. The stability at room temperature demonstrated that the hybrid material could be useful as a potential candidate for photoactive thin films in organic devices.